(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
This paper aim to generate and take Action potential signal (AP) then converts it to digital signal based on one bit Sigma-Delta converter (?-?) to produce a 1-bit stream represent this signal with resolution of 10 bit. This data has been stored in proposed memory created in electronic device called Field Programmable Gate Array (FPGA) by which also the proposed converter had been designed and implemented practically. Finally, the obtained results analyzed and compared with other converter techniques to show the difference in the results and performance